Active screen time and imagination in 5–6-years-old children - Bukhalenkova, Daria; Almazova, Olga (Frontiers in Psychology, 2023)
This research focused on the connection between such factors of the active screen time of preschoolers as the time spent playing computer games and parental participation in children's computer games on imagination in 5-6 years old children. The mothers of 772 children were asked to fill out questionnaires where they described how their children interact with gadgets. 371 of these children also participated in the test that assessed productive imagination using complete the drawing task (such parameters as flexibility, originality, elaboration were assessed). As a result of the study, no relationship was found between imagination and the time spent by preschoolers playing computer games. At the same time, this study revealed significant relationships between imagination and the characteristics of parental participation in the gadgets' usage by preschoolers. The research showed that imagination flexibility scores are significantly higher in children who use gadgets with siblings or peers than in those who often play alone or with an adult.